Unraveling the impact of self-esteem on the utilization of Instagram filters: the mediating role of fear of negative evaluation - Lo Destro, Calogero (Frontiers in Psychology, 2024)
The popularity of social media platforms, such as Instagram, has given rise to a surge in photo editing and filtering practices among users. Understanding the underlying psychological factors that drive individuals to employ filters is crucial in comprehending the impact of such behavior on self-perception and online interactions. This study aims to investigate the influence of self-esteem on the importance attributed to the use of Instagram filters, with a particular focus on the mediating role played by the fear of negative evaluation. A sample of participants (N = 2,657) from diverse demographic backgrounds has been recruited to complete a series of questionnaires measuring self-esteem, fear of negative evaluation, and Instagram filter usage patterns. Mediation analysis has been employed to assess the extent to which the fear of negative evaluation mediates the relationship between self-esteem and filter usage importance. In line with the hypotheses, the results revealed that participants self-esteem negatively predicted fear of negative evaluation, which in turn had a positive effect on use of filters. Furthermore, fear of negative evaluation fully mediated the relationship between self-esteem and use of filters. Overall, the implications of this research extend to both theoretical and practical domains. The findings can contribute to the existing literature on self-esteem, social media behavior, and body image by shedding light on the factors influencing digital self-presentation.